Ngeloop Haga Puasa: Praktik Sosial Budaya Menyambut Ramadan untuk Penguatan Identitas Muslim - Napsiah Napsiah (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
The practice of “Ngeloop” (bathing and soaking in seawater) when welcoming Ramadan fasting is a tradition of the South Lampung ethnic group. But in practice, this tradition is not only carried out by the South Lampung ethnic group, but also other ethnic groups that are Muslim. This research aims to determine the actions of Muslims in Lampung in carrying out the local tradition of “Ngeloop Haga Puasa”. This research was a descriptive qualitative research with interview and observation methods. The informants were selected using the purposive sampling and snowball sampling technique. The location of the research was conducted in Kalianda, South Lampung District, Lampung Province, Indonesia. The results of the research concluded that the religious value which obliges Muslims to practice fasting has been internalized which is expressed in the form of the practice of ngeloop. Expression in the form of local cultural practices is a strengthening of Muslim identity in South Lampung.